IMPLEMENTATION OF THE CONCEPT AND THEORY OF MANAGEMENT FUNCTIONS IN EFFORTS TO IMPROVE QUALITY - Sumadi Sumadi; Nico Irawan; Muhammad Hasan Ma'ruf (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Implementation of madrasa management contains two aspects of study, first the assessment in the conceptual setting of an approach in running a particular business in the education segment that seeks to maximize competitiveness through continuous improvement of products, people, processes, and organizational environments or institutions, and both studies cover the way they are delivered, which includes ten characteristics from i.e. customer focused (internal and external); obsessed with quality; use scientific approach; continuously improving quality; education and training; exercising controlled freedom; have unity of purpose; as well as involving and empowering educators and students. Both aspects must become a unified whole so that efforts to achieve goals can be obtained optimally. Keywords: Madrasa Management, Madrasa Quality, Management Function